HARMONISASI PENGATURAN PERIZINAN BERUSAHA BERBASIS RISIKO (OSS-RBA) DENGAN KETENTUAN RTRW PROVINSI BALI DALAM PERLINDUNGAN KAWASAN LINDUNG - Ni Komang Merlinda Putri; I Kadek Dony Hartawan; Ni Komang Irma Adi Sukmaningsih (Universitas Pendidikan Ganesha, 2026)
The reform of Indonesia’s business licensing system through Risk-Based Business Licensing as regulated under Goverment Regulation No. 5 of 2021 aims to establish a conducive investment climate by simplifying licensing procedures based on the level of risk associated with the business activity. Nevertheless, the implementation of business licensing must remain consistent with spatial planning as stipulated under the regulations in Goverment Regulation No. 21 of 2021 concerning Spatial Planning Administration and the Bali Provincial Regulatian Number 2 of 2023 concerning the Bali Provincial Spatial Plam (RTRW) for 2023-2043, particularly regarding the protection of conservation areas. This research is motivated by the potential disharmony between the regulation Risk-Based Business Licensing and spatial palnning provisions, particularly in connection with the issuance of busniness licenses within areas adjacent to protected areas. This issue is reflected in the business activities associated with the issuance of Business Identification Number (NIB) through the Online Single Submission Ris-based Approach (OSS-RBA) system in the Pemutih Beach ares, Pecatu Village, Badung Regency, raising questions regarding the comformity of licensing system with the applicable spatial planning regulations. this study is intended to analyze the harmonization between the regulation of Risl-based Business Licensing and the Bali Provincial Spatial Plan in protecting conservation areas, as well as to examine the consistency among Goverment Regulation No. 5 of 2021, Goverment Regulation No. 21 of 2021, and Bali Provinsiap Regulation No. 2 of 2023 in ensuring legal certainly a normative legal research method using both the statutory approach and the conseptual approach, with qualitative analysis based on library research. The findings of this study are expected to contribute to the harmonization of business licensing plicies and spatial planning regulations in order to ensure legal certaintywhile safeguarding protectedareas as part of sustainable development